RE-INISIASI DETONASI DI BELAKANG PLAT DENGAN ORIFIS GANDA 7 MM - Naryanto, Rizqi Fitri (Lembaga Penelitian & Pengabdian Kepada Masyarakat (LPPM), IST AKPRIND Yogyakarta, 2012)
Detonation waves are the combustion reaction waves that propagate at supersonic speeds. The phenomenon of detonation waves that have failed due to the diffraction process which can re-initiatited was back into a detonation wave, interesting to understand that this problem related to the safety of hydrogen gas. This study aims to understand of failure mechanisms and re-initiation of detonation wave behind the plate with double orifices 7mm. This experiment use a Detonation Test Pipe (DTP) with 6 meters length, DTP is divided into two parts, namely 1 meter for the driver test pipe and 5 meters to the driven test pipe. Aluminum plate with double orifices diameter of 7 mm and the distance between the orifices 14 mm,10 mm thickness on the driven test at 5 meters distance from the ignition point. Two mechanisms re-initiation behind the detonation wave propagation test models can be classified as follows: (1) Re-initiation detonation by DDT in down stream area. (2) Re-initiation detonation by shock-wall, re-initiation detonation by interaction between wall pipe and shock wave. Quenching detonation (deflagration) observed at initial pressure of 20kPa, while the initial pressure of 30 - 60kPa re-initiation detonation occurred in the presence of DDT process in the downstream. Re-initiation detonation wave due to interaction between shock wave with the inner wall pipe occurs at the initial pressure of 70-100kPa characterized by the formation of fine smaller detona-tion cells. To guaranty to make quenching detonation (deflagration), pressure must be in the low pressure at 20kPa to design detonation arrester.